Effects of ultrasound on the degradation kinetics, physicochemical properties and prebiotic activity of Flammulina velutipes polysaccharide - Jinrong Xiao; Xin Chen; Qiping Zhan; Lei Zhong; Qiuhui Hu; Liyan Zhao (Ultrasonics Sonochemistry, 2022)
The controllable ultrasonic modification was hindered due to the uncertainty of the relationship between ultrasonic parameters and polysaccharide quality. In this study, the ultrasonic degradation process was established with kinetics. The physicochemical properties and prebiotic activity of ultrasonic degraded Flammulina velutipes polysaccharides (U-FVPs) were investigated. The results showed that the ultrasonic degradation kinetic models were fitted to 1/Mt-1/M0 = kt. When the ultrasonic intensity increased from 531 to 3185 W/cm2, the degradation proceeded faster. The decrease of polysaccharide concentration contributed to the degradation of FVP, and the fastest degradation rate was at 60 °C. Ultrasound changed the solution conformation of FVP, and partially destroyed the stability of the triple helix structure of FVP. Additionally, the viscosity and gel strength of FVP decreased, but its thermal stability was improved by ultrasound. Higher ultrasonic intensity led to larger variations in physicochemical properties. Compared with FVP, U-FVPs could be more easily utilized by gut microbiota. U-FVPs displayed better prebiotic activity by promoting the growth of Bifidobacterium and Brautella and inhibiting the growth of harmful bacteria. Ultrasound could be effectively applied to the degradation of FVP to improve its physicochemical properties and bioactivities.